HIV transmission and retention in care among HIV‐exposed children enrolled in Malawi's prevention of mother‐to‐child transmission programme. Issue 1 (4th September 2017) - Haas, Andreas D.; van Oosterhout, Joep J.; Tenthani, Lyson; Jahn, Andreas; Zwahlen, Marcel; Msukwa, Malango T; Davies, Mary‐Ann; Tal, Kali; Phiri, Nozgechi; Spoerri, Adrian; Chimbwandira, Frank; Egger, Matthias; et al.
Abstract: Introduction : In Malawi, HIV‐infected pregnant and breastfeeding women are offered lifelong antiretroviral therapy (ART) regardless of CD4 count or clinical stage (Option B+). Their HIV‐exposed children are enrolled in the national prevention of mother‐to‐child transmission (PMTCT) programme, but many are lost to follow‐up. We estimated the cumulative incidence of vertical HIV transmission, taking loss to follow‐up into account. Methods : We abstracted data from HIV‐exposed children enrolled into care between September 2011 and June 2014 from patient records at 21 health facilities in central and southern Malawi. We used competing risk models to estimate the probability of loss to follow‐up, death, ART initiation and discharge, and used pooled logistic regression and inverse probability of censoring weighting to estimate the vertical HIV transmission risk. Results : A total of 11, 285 children were included; 9285 (82%) were born to women who initiated ART during pregnancy. At age 30 months, an estimated 57.9% (95% CI 56.6–59.2) of children were lost to follow‐up, 0.8% (0.6–1.0) had died, 2.6% (2.3–3.0) initiated ART, 36.5% (35.2–37.9) were discharged HIV‐negative and 2.2% (1.5–2.8) continued follow‐up. We estimated that 5.3% (95% CI 4.7–5.9) of the children who enrolled were HIV‐infected by the age of 30 months, but only about half of these children (2.6%; 95% CI 2.3–2.9) were diagnosed. Conclusions : Confirmed mother‐to‐child transmission rates were low, but due to poor retention only about half of HIV‐infected children were diagnosed. Tracing of children lost to follow‐up and HIV testing in outpatient clinics should be scaled up to ensure that all HIV‐positive children have access to early ART.